Factors Associated With Marital Instability Among Rural Farming Households in Akwa Ibom State, Nigeria - Asa, U. A; Nkan, V. V (European Scientific Journal, ESJ, 2017)
In this paper, we investigated factors associated with marital instability in rural households. Using a case study of rural farming households in Akwa Ibom State, Nigeria, we examined the demographic characteristics of married couples in rural farming households and the nature of marital instability among them in addition to ascertaining the factors associated with marital instability in the study area. Descriptive statistics and factor analysis were employed to analyze data collected from 240 married couples selected using a multi-stage sampling procedure. Results revealed that the average age of the respondents was 42 years; 91.7% of them were functionally literate; their average household size comprised of six persons; and seventeen years was their average years of marriage. Findings also revealed that majority of the respondents had low marital instability; factor analysis result showed that socio-cultural difference, psychological factor, economic factor, marriage-based factor, health factor, sex-related factor, conflict factor and communication-based factor were the major factors associated with marital instability among married persons in the study area. The findings highlight avenues of theoretical development to better understand marital instability among rural dwellers in Nigeria as well as have implications for marriage counselling among married persons in the study area.